Perceptions du rôle de l’interprète en contexte de formation internationale - Woroch, Justyna (Studia Romanica Posnaniensia, 2024)
This study explores the presence of community interpreters in lifelong learning contexts where adult learners engage in international education. It aims to uncover how adult learners perceive interpreters’ roles in educational settings through an online questionnaire. The research identifies interpreter roles, using Tryuk’s (2004) framework for community interpretation. It finds similarities between educational and community interpretation settings. Participants emphasize interpreters’ vital role in facilitating international education, ensuring accessibility, and reducing language-related stress. However, some note that interpreters can unintentionally introduce stress, especially without professional competence. Overall, this study provides pilot insights into adult learners’ perceptions of interpreters in educational contexts, revealing the complex dynamics of interpretation in international education.